2005
DOI: 10.1093/aob/mci261
|View full text |Cite
|
Sign up to set email alerts
|

Oxaziclomefone, a New Herbicide, Inhibits Wall Expansion in Maize Cell-cultures without Affecting Polysaccharide Biosynthesis, Xyloglucan Transglycosylation, Peroxidase Action or Apoplastic Ascorbate Oxidation

Abstract: OAC decreased wall extensibility without influencing the synthesis or post-synthetic modification of major architectural wall components, or the redox environment of the apoplast. The possible value of OAC as a probe to explore aspects of primary cell wall physiology is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…To exert its toxicity in plant cells, DM first needs to pass through the cell wall. Several studies have shown that both biotic stresses (e.g., bacteria, fungi, and virus) and abiotic stresses (metals, pesticide, UV–B, and temperature) may alter the composition of cell wall by inducing a thickening of cuticles or trichomes. , The present study confirms that the herbicide DM may strongly affect the cell wall of O. sativa . Our results show that a 48-h exposure to trace DM concentrations may increase the proportion of uronic acid and polysaccharides in cell wall fractions (SI Figure SI.2A, B) and induce the transcription of various genes involved in the biosynthesis of cell wall ( pectin methylesterase , pectinesterase , cellulose synthase , phenylalanine ammonia-lyase genes) (SI Figure SI.2C; Table SI.1 and SI.2).…”
Section: Discussionsupporting
confidence: 85%
“…To exert its toxicity in plant cells, DM first needs to pass through the cell wall. Several studies have shown that both biotic stresses (e.g., bacteria, fungi, and virus) and abiotic stresses (metals, pesticide, UV–B, and temperature) may alter the composition of cell wall by inducing a thickening of cuticles or trichomes. , The present study confirms that the herbicide DM may strongly affect the cell wall of O. sativa . Our results show that a 48-h exposure to trace DM concentrations may increase the proportion of uronic acid and polysaccharides in cell wall fractions (SI Figure SI.2A, B) and induce the transcription of various genes involved in the biosynthesis of cell wall ( pectin methylesterase , pectinesterase , cellulose synthase , phenylalanine ammonia-lyase genes) (SI Figure SI.2C; Table SI.1 and SI.2).…”
Section: Discussionsupporting
confidence: 85%
“…So far, the MoA of oxaziclomefone has remained elusive 35,36 and it is therefore classified in the HRAC class 0. Here, we present data on oxaziclomefone that show strong FAT thermal stabilization, strong FAT binding in the active center, strong inhibition of FFA production in the FAT activity assay and the clear FAT-like fingerprint in the P-Profile.…”
Section: Discussionmentioning
confidence: 99%
“…Even neutral sugars can be analysed by PE if a borate buffer is used, with which the sugar reversibly forms an anionic borate ester (e.g. O ' Looney & Fry 2005 ). Electrophoretic mobility depends on both the charge ( Q ) of the compound (which at pH 6.5 will be about − 1 in the case of GalA and GlcA → Man, and nearly − 2 in the case of GalA → GalA) and its molecular weight ( M r ).…”
Section: Paper E Lectrophoresis ( Pe )mentioning
confidence: 99%